Variation in Spanish /s/: Overview and New Perspectives - Eva Núñez-Méndez (Languages, 2022)
The natural tendency for language variation, intensified by Spanish’s territorial growth, has driven sibilant changes and mergers across the Spanish-speaking world. This article aims to present an overview of the most significant processes undergone by sibilant /s/ in various Spanish-speaking areas: devoicing, weakening, aspiration, elision, and voicing. Geographically based phonetic variations, sociolinguistic factors, and Spanish language contact situations are considered in this study. The sibilant merger and its chronological development in modern Spanish, along with geographic expansion, have resulted in multiple contemporary dialectal variations. This historical lack of stability in these sounds has marked modern regional variations. Tracing and framing the sibilants’ geo-linguistic features has received much attention from scholars, resulting in sibilants being one of the most studied variables in Spanish phonetics. In this article, we provide a concise approach that offers the reader an updated sociolinguistic view of the modern cross-dialectal realizations of /s/. It is essential to study sibilant development to describe Spanish dialects, the differences between Transatlantic and Castilian varieties, and the speech features found in Spanish speaking communities in the Americas. Examining sibilance from different approaches with a representative variety of Spanish dialects as examples advances the importance of sociolinguistic phenomena to index language changes.